Development of a Digital Live Worksheet in the Religion Subject to Improve Student Learning Outcomes at Junior High School: Pengembangan Digital Live Worksheet pada Mapel PAI untuk Meningkatkan Hasil Belajar Peserta Didik di SMP - M Fajar Sidik; Eni Fariatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
The development of digital live worksheets is a form of innovation to improve student learning outcomes. This study has a problem formulation, how, the practicality, and effectiveness of the digital live worksheet developed on the material of the angels of Allah SWT able to improve student learning outcomes. This research is a type of development research based on the theory of Dick and Carey. Products developed from 3 aspects, feasibility, practicality, and effectiveness. Feasibility was measured by 3 experts, practicality using questionnaires and observations, and effectiveness was measured by T Test statistics using the SPSS program. SMPN 2 Buduran was selected with 2 classes, VII B and VII D as the sample with the sample selection technique using purposive sampling. The results showed 97.91% with a very decent category. 95.2% with easy and practical categories according to users, namely Class VII B students of SMPN 2 Buduran. And a significance score of 0.000 with t arithmetic > t table (10.611>2.0345) and p-value (0.000<0.05) proves that the digital live worksheet is effective in improving student learning outcomes at SMPN 2 Buduran.